Proteomic Analysis of Preoperative CSF Reveals Risk Biomarkers of Postoperative Delirium - Han, Yongzheng; Chen, Wei; Song, Yanan; Yuan, Yi; Li, Zhengqian; Zhou, Yang; Liu, Taotao; Han, Dengyang; Mi, Xinning; Li, Min; Wang, Geng; Zhong, Lijun; et al. (Frontiers in Psychiatry, 2020)
Objective: To analyze the proteome of preoperative cerebrospinal fluid (CSF) in older orthopedic patients with or without postoperative delirium (POD) using untargeted proteomics. Methods: A prospective cohort study was conducted. Eighty hip fracture patients aged ≥ 65 years were recruited. After successful spinal anesthesia, CSF was collected. The patients were divided into POD and No-POD groups based on the Confusion Assessment Method, and patients with POD were graded using the Memorial Delirium Assessment Scale (MDAS). Thirty No-POD patients were matched to 10 POD patients by age (± 2 years) and Mini–Mental State Examination score (± 2 scores). Label-free proteomic analysis was performed using a liquid chromatography coupled to mass spectrometry (LC-MS) workflow. Validation was performed using mass-spectrometry-based parallel reaction monitoring (PRM) for the 30 No-POD and 10 POD patients, as well as for an additional 5 POD patients. Bioinformatics were used to investigate possible relevant pathological mechanisms. Results: The incidence of POD in older orthopedic patients was 18.8% in our cohort of 80 patients. Proteomics results revealed 63 dysregulated CSF proteins, and PRM analysis validated these results. The preoperative CSF levels of both V-set and transmembrane domain-containing protein 2B (VSTM2B) and coagulation factor V (FA5) were positively correlated with MDAS scores on postoperative day 1 (r > 0.8, p < 0.05). Bioinformatic analysis revealed that several nervous-system-related pathways are relevant to POD development. Conclusion: We identified and validated several novel CSF proteins that are dysregulated in POD, and revealed several pathways that are relevant to POD development. Our results not only provide risk biomarkers for POD, but also give clues for further investigations into the pathological mechanisms of delirium. Clinical trial registration: This study was registered in the Chinese Clinical Trial Registry (ChiCTR1900021533).